Frontispiece: Beating Vesicles: Encapsulated Protein Oscillations Cause Dynamic Membrane Deformations. Issue 50 (4th December 2018) - Litschel, Thomas; Ramm, Beatrice; Maas, Roel; Heymann, Michael; Schwille, Petra
Abstract : Synthetic Biology In their Communication onpage 16286 ff., P. Schwille et al. report that the encapsulation of Min proteins in giant liposomes leads to oscillatory, spatiotemporal reaction–diffusion patterns on the vesicle membranes and oscillations in the overall shapes of the vesicles.